Effect of filler wires and direct ageing on the microstructure and mechanical properties in the multi-pass welding of Inconel 718. (April 2015) - Devendranath Ramkumar, K.; Jagat Sai, R.; Santhosh Reddy, V.; Gundla, Sridhar; Harsha Mohan, T.; Saxena, Vimal; Arivazhagan, N.
Highlights: Combined effects of current pulsing, filler wires and ageing heat treatment in the control of laves phase of Inconel 718 welds have been addressed. Reduced unmixed zone upon ageing treatment. Improved weld tensile properties exhibited by ERNiCr-3 filler upon ageing heat treatment. Abstract: This paper investigates the weldability, microstructure and mechanical properties of 5 mm thick Inconel 718 plates obtained by pulsed current gas tungsten arc welding (PCGTAW) using ERNiCu-7, ERNiCrCoMo-1 and ERNiCr-3 fillers. Post weld heat treatment (PWHT) was also carried out at 720 °C/8 h/furnace cooling followed by 620 °C/8 h/air cooling on the weldments. A comparative evaluation based on the microstructure features and mechanical properties of both the as-welded and aged samples were studied. Further this study addressed the combined effect of filler wires and post weld heat treatment on the metallurgical and mechanical properties of the weldments. The studies showed the improvement in tensile strength and drop in impact toughness for all the weldments after direct ageing heat treatment.